An Assay For Corundum By Mechanical Analysis. - W. Spencer Hutchinson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1913)
IT is the purpose of this paper to describe a method used to determine the corundum contents of samples of hard crystalline gneiss containing both corundum and red garnet. A chemical analysis of the rock for alumina would not fix the amount of corundum because at least three other constituent minerals of the rock, mica, feldspar, and garnet, contain alumina combined with silica. Following are the principal minerals found in the samples, together with their specific gravity and hardness as given by Dana: